FINANCING OF INNOVATION ACTIVITIES (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In this paper, you can see the reviews the theoretical and empirical economic literature on innovation financing and draws some policy conclusions to address some of the challenges. Asymmetric information and moral hazard theories as applied to innovation financing are then reviewed, followed by a summary of empirical evidence on the topic. The final section discusses implications for public policy.”